The Design Concept of Road Median Based on Lampung Culture - Satria, Widi Dwi; Franjaya, Eduwin Eko; Sitompul, Rabita Akbari (Universitas Aisyiyah Yogyakarta, 2024)
The road median is a supporting feature in the road environment, where it can be used as a landscape design medium to construct an image of the city and express a certain aesthetic experience in addition to serving as a traffic barrier. To have a value and message transmitted in a design, the road median requires a mature concept. Sultan Agung Street is a major thoroughfare in the city of Bandar Lampung, with a large volume of traffic. The government has not completely regulated the two-lane roadways with a median road on Sultan Agung Street. The road median of Sultan Agung Street, which is positioned in a prominent location Bandar Lampung's city, should be able to convey local culture. However, based on the existing state of the road median, no median layout or design that depicts Lampung culture has been discovered. The goal of this research was to examine and determine the Lampung culture notion that may be used to Sultan Agung Street's median. The descriptive qualitative research approach was utilized to identify the size of the site and the cultural themes that will be converted into design concepts by collecting field data. The study's findings are presented in the form of thoughts and sketches for the physical architecture of Sultan Agung Street's median, which incorporates local cultural philosophy. The tapis motif, the construction of the siger, as well as the idea of sailing ships and Lampung ethnic dances are all incorporated into the design.